β(3)-Adrenergic Receptor Stimulation Induces E-Selectin-mediated Adipose Tissue Inflammation - Roth Flach, Rachel J. (American Society for Biochemistry and Molecular Biology, 2013)
Inflammation induced by wound healing or infection activates local vascular endothelial cells to mediate leukocyte rolling, adhesion, and extravasation by up-regulation of leukocyte adhesion molecules such as E-selectin and P-selectin. Obesity-associated adipose tissue inflammation has been suggested to cause insulin resistance, but weight loss and lipolysis also promote adipose tissue immune responses. While leukocyte-endothelial interactions are required for obesity-induced inflammation of adipose tissue, it is not known whether lipolysis-induced inflammation requires activation of endothelial cells. Here, we show that β(3)-adrenergic receptor stimulation by CL 316,243 promotes adipose tissue neutrophil infiltration in wild type and P-selectin-null mice but not in E-selectin-null mice. Increased expression of adipose tissue cytokines IL-1β, CCL2, and TNF-α in response to CL 316,243 administration is also dependent upon E-selectin but not P-selectin. In contrast, fasting increases adipose-resident macrophages but not neutrophils, and does not activate adipose-resident endothelium. Thus, two models of lipolysis-induced inflammation induce distinct immune cell populations within adipose tissue and exhibit distinct dependences on endothelial activation. Importantly, our results indicate that β(3)-adrenergic stimulation acts through up-regulation of E-selectin in adipose tissue endothelial cells to induce neutrophil infiltration.